2020
DOI: 10.1371/journal.pcbi.1007827
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions can create persistent fluctuations in high-diversity ecosystems

Abstract: When can ecological interactions drive an entire ecosystem into a persistent non-equilibrium state, where many species populations fluctuate without going to extinction? We show that high-diversity spatially heterogeneous systems can exhibit chaotic dynamics which persist for extremely long times. We develop a theoretical framework, based on dynamical meanfield theory, to quantify the conditions under which these fluctuating states exist, and predict their properties. We uncover parallels with the persistence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 30 publications
(51 reference statements)
7
98
0
Order By: Relevance
“…S1). Our results suggest that persistent fluctuations and high diversity require and allow each other, as theoretically shown in previous work (32,33).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…S1). Our results suggest that persistent fluctuations and high diversity require and allow each other, as theoretically shown in previous work (32,33).…”
supporting
confidence: 87%
“…May and others have suggested that large or strongly interacting communities will generically be unstable (20)(21)(22)(23)(24)(25)(26)), yet we still do not understand how such large communities may arise, nor the dynamical behavior of communities that are not stable. In particular, it has been shown that species can go extinct before the community loses stability (27)(28)(29)(30), and also that unstable communities can display a range of dynamics including periodic (limit cycle) oscillations or chaotic fluctuations, that in some cases play a role in sustaining diversity (31)(32)(33)(34)(35)(36)(37). This body of theory has however been difficult to validate because driving parameters such as ecological interactions are often challenging to estimate (38,39).…”
mentioning
confidence: 99%
“…On the other hand, non-equilibrium coexistence theory suggests that fluctuations can also enhance the coexistence of interacting species (Barab as, D'Andrea & Stump, 2018). Thus, while May (1972) envisioned the instability of complex communities as a limitation, Roy et al (2020) recently showed that the selfsustaining fluctuations of such communities can also enable more species to coexist. With arguments paralleling biological insurance theory, they identified conditions under which population responses become asynchronous and differentiated, leading to more species persisting in a chaotic state than at equilibrium.…”
Section: Future Challengesmentioning
confidence: 99%
“…The negative association between temporal turnover and long-term conservation value likely arises due to the fact that turnover in the model is purely autonomous, driven by ecological interactions and dispersal (O'Sullivan et al, 2021) as opposed to external processes such as abiotic fluctuations or regional-scale invasions. Autonomous turnover requires ecological redundancy as well as spatial connectivity to function; without a pool of species in adjacent sites capable of passing through local abiotic filters, communities converge on fixed points in the absence of external driving forces (Roy et al, 2020;Pearce et al, 2020;O'Sullivan et al, 2021). Those sites undergoing rapid autonomous turnover have least impact on regional diversity since the ecological redundancy required for steady state dynamics means the metacommunity can readily respond to their loss.…”
Section: Long-term Shifts In Regional Diversitymentioning
confidence: 99%